Phytochemical Analysis and Multifaceted Biomedical Activities of Nitraria retusa Extract as Natural Product-Based Therapies - Manal M. Khowdiary; Zinab Alatawi; Amirah Alhowiti; Mohamed A. Amin; Hussam Daghistani; Faisal Miqad K. Albaqami; Mohamed Ali Abdel-Rahman; Ahmed Ghareeb; Nehad A. Shaer; Ahmed M. Shawky; Amr Fouda (Life)
This study examined the phytochemical profile and biomedical activities of Nitraria retusa, a halophytic and drought-resistant shrub. HPLC analysis showed gallic acid (1905.1 μg/g), catechin (1984.1 μg/g), and ellagic acid (2671.1 μg/g) as the primary constituents, while FT-IR analysis revealed a complex organic profile with significant functional groups. The extract demonstrated strong antioxidant activity in DPPH assays, outperforming ascorbic acid (IC50 = 18.7 ± 1.0 μg/mL) with an IC50 of 16.4 ± 4.4 μg/mL. It demonstrated specific antiproliferative effects on cancer cell lines as it showed selective cytotoxicity against cancer cell lines; normal WI38 cells were largely unaffected, showing 50.0% viability at 125 μg/mL. The most sensitive cell line was Caco2, which showed 50.0% viability at 125 μg/mL. Anti-diabetic properties were exhibited by means of inhibition of α-amylase (IC50 = 68.2 ± 4.2 μg/mL) and α-glucosidase (IC50 = 22.8 ± 3.3 μg/mL). Additionally, antimicrobial activity was observed to be broad-spectrum, and it was most effective against E. coli (32.6 mm inhibition zone at 400 μg/mL) and Penicillium glabrum (35.3 mm at 400 μg/mL). These findings highlight the potential of N. retusa in developing plant-based therapeutic approaches.